STUDY ON ANTI-MICROBIAL PROPERTIES OF Enicosanthum membranifolium SINCLAIR AND Enicosanthum cupulare (KING) AIRY-SHAW - Efdi, Mai; Koketsu, Mamoru; Watanabe, Kunitomo; -, Nurainas (Universitas Andalas, 2009)
ABSTRACT n-Hexane and ethyl acetate fractions of methanol extracts of two species of Annonaceae, Enicosanthum membranifolium Sinclair and Enicosanthum cupulare (King) Airy-Shaw, were screened for antimicrobial activity against eighteen bacterial strains using agar dilution method. The ethyl acetate fraction of the two Annonaceae plants showed higher antimicrobial activities than the n-hexane fraction. The extracts of the plants tested were significantly more active against gram-positive with minimum inhibitory concentration (MICs) ranging from 0.0625 to 4 mg/mL than against gram negative bacteria (MICs >4 mg/mL). Keywords: Antibacterial activity; Enicosanthum membranifolium Sinclair; Enicosanthum cupulare (King) Airy-Shaw